Analisis Pengelolaan Program Corporate Social Responsibility (CSR) di Desa Gunungputri Kecamatan Gunung Putri Kabupaten Bogor - Azzahro, Siti; Purnamasari, Hanny; Gumilar, Gun Gun (Peneliti.net, 2025)
Research on the Corporate Social Responsibility (CSR) management program in Gunung Putri Village, Gunung Putri District, Bogor Regency, with a focus on the clean water program implemented by PT Indocement Tunggal Prakasa Tbk. Law Number 6 of 2014 concerning Villages is the main basis for this approach, emphasizing the importance of equitable economic development throughout society, including in rural areas. Article 78 of the law emphasizes the main objectives of village development to improve the quality of life of the community, reduce poverty, and maintain environmental sustainability.The research also looked at PT Indocement's involvement in village development through CSR programs, with a focus on developing clean water infrastructure in 12 villages around their factory in Citeureup. Although there are positive achievements such as their commitment to social responsibility, there are also significant obstacles such as a lack of coordination with the village government and the complexity of program implementation. This study recommends increased communication and active cooperation between companies, local governments, and local communities to ensure the success and desirability of these CSR programs. Thus, this research not only provides an in-depth understanding of the implementation of CSR programs in a village context, but also highlights the importance of effective management and active participation from all parties in supporting sustainable development and having a positive impact on the welfare of local communities.